2019
DOI: 10.24820/ark.5550190.p010.924
|View full text |Cite
|
Sign up to set email alerts
|

Isoparametricity and related phenomena in reactions of trans-2,3-diaryloxiranes with arenesulfonic acids

Abstract: This article is a continuation of a series of publications devoted to the systematic study of the still poorly investigated unique isoparametricity phenomenon in chemistry. Quantitative evidence for all variants of the second-order interaction structure-structure and structure-temperature types were obtained in the reactions between X-substituted trans-2,3-diaryloxiranes and Y-substituted arenesulfonic acids. Experimental evidence for the reality of isoparametric points with respect to the parameters of variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In reactions of aryloxiranes with arenesulfonic and arenecarboxylic acids the interactions structure-structure and structure-temperature types were clearly manifested, [7][8][9][10] which made it possible to obtain convincing experimental evidence of the isoparametricity phenomenon. Of particular importance is the proof of the physical reality of such an aspect of isoparametricity as the widely discussed enthalpy-entropy compensation effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reactions of aryloxiranes with arenesulfonic and arenecarboxylic acids the interactions structure-structure and structure-temperature types were clearly manifested, [7][8][9][10] which made it possible to obtain convincing experimental evidence of the isoparametricity phenomenon. Of particular importance is the proof of the physical reality of such an aspect of isoparametricity as the widely discussed enthalpy-entropy compensation effect.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular importance is the proof of the physical reality of such an aspect of isoparametricity as the widely discussed enthalpy-entropy compensation effect. [8][9][10] Our recent study [11] showed that in the catalyzed by Z-substituted pyridines reaction of phenyloxirane with such representative of NH acids as N-benzoylbenzenesulfonamide, there was no interaction between the effects of substituents Z and temperature. This reaction turned out to be isoenthalpic with respect to variation of substituents Z (ΔHZ ‡ = const, δZΔH ‡ = 0).…”
Section: Introductionmentioning
confidence: 99%